Manejo de lagartas e percevejos da soja com controle localizado - Aita, Valmir (2013)
Soybean [Glycine max (L.) Merrill] is the most important crop grown in Brazil and worldwide. Nevertheless, the yield is still limited by several issues in which the damages by caterpillars and stink bugs are main ones if not controlled efficiently. The pest control is usually achieved by insecticide application, which results in an increased production cost, disturb biological control, and causes contamination in harvest and environment, so it is necessary to develop news techniques aiming to reduce the amount of sprayed insecticides. The preset study was carried out in five soybean grown areas during 2010/11 and 2011/12. This experiment aimed to analyze the spatial and temporal distribution in order to perform site-specific control of caterpillars and stink bugs by using agriculture-precision tools for mapping and control of insects. In addition, the technical and economic effects of this approach were surveyed. The first chapter shows the site-specific control for caterpillars while the chapter two for stink bugs. The population of soybean caterpillars can be suppressed by site-specific approach where the population exceeds the economic threshold and therefore saving insecticide. The site-specific control for stink bugs in soybean allows save insecticide and decreases the bugs population, but causes outbreaks far beyond the economic threshold. Economically speaking, the site-specific control of caterpillars and stink bugs is possible, but requires further studies to optimize the sampling procedure.